2004
DOI: 10.1097/00000542-200412000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and Desflurane Impair Right Ventricular–Pulmonary Arterial Coupling in Dogs

Abstract: Isoflurane and desflurane markedly impair RV-PA coupling efficiency in dogs, during hyperoxia and hypoxia, both by increasing RV afterload and by decreasing RV contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…However, there were more severe patients undergoing RA, indicated by both haemodynamics and the fact that significantly more patients on specific PAH therapy received RA than GA. The use of GA may increase PVR through several mechanisms, including increased sympathetic stimulation during airway instrumentation on laryngoscopy [39], effects of volatile agents [40], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [12,13], hypoxia [15] and hypercapnia [16]. The present data suggested that more complications occurred in those with higher PET,CO 2 and peak airway pressure, although many confounding factors may affect these values.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, there were more severe patients undergoing RA, indicated by both haemodynamics and the fact that significantly more patients on specific PAH therapy received RA than GA. The use of GA may increase PVR through several mechanisms, including increased sympathetic stimulation during airway instrumentation on laryngoscopy [39], effects of volatile agents [40], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [12,13], hypoxia [15] and hypercapnia [16]. The present data suggested that more complications occurred in those with higher PET,CO 2 and peak airway pressure, although many confounding factors may affect these values.…”
Section: Discussionmentioning
confidence: 60%
“…The present data suggested that more complications occurred in those with higher PET,CO 2 and peak airway pressure, although many confounding factors may affect these values. Volatile anaesthetic agents may also adversely affect right ventricular preload and contractility [25], as well as afterload [40], although isoflurane has been used safely in human PAH [41]. Desflurane appears to exert worse pulmonary vascular effects than isoflurane, probably through sympathetic activation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate recorded in patients who underwent general anaesthesia might be explained by a downwards spiral of worsening right ventricular function. Indeed, general anaesthesia may increase PVR through several mechanisms including increased sympathetic stimulation during airway instrumentation and tracheal intubation [19], effects of volatile agents used for anaesthesia [20], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [21] and hypoxic pulmonary vasoconstriction caused by alveolar hypoxia [22].…”
Section: Discussionmentioning
confidence: 99%
“…Table 7 shows the effect of various anaesthetic agents on right ventricular contractility and afterload. Inhaled anaesthetics such as isoflurane and desflurane have a marked dose-dependent effect in reducing right ventricular contractility and some negative impact on right ventricular afterload; hence, they significantly impair right ventricle pulmonary artery coupling [46,47]. Sevoflurane causes significant depression of global right ventricular function associated with a qualitatively different effect on inflow and outflow tracts, without any modification of pulmonary vascular resistance [48].…”
Section: Principles Of Anaesthetic Managementmentioning
confidence: 99%